SOIL AND CLIMATE DETERMINE ANTIOXIDANT CAPACITY OF WALNUTS - Figueroa, Fernando; Marhuenda, Javier; Gironés-Vilaplana, Amadeo; Villaño, Débora; Villaño, Adela; Mulero, Juana; Cerdá, Begoña; Zafrilla, Pilar (Emirates Journal of Food and Agriculture, 2017)
Factors as variety, soil and climatic conditions can influence the nutritional composition of walnuts and its resultant biological activity. The aim of this work was to study the influence of soil and climate factors in the antioxidant capacity of 10 different varieties of nuts, obtained from two experimental cultivars with different weather and soil conditions. Ten different varieties of walnut samples were obtained from two experimental cultivars, analyzing the antioxidant capacity by ORAC, DPPH• and ABTS+ methods. Eureka and Tehama walnuts showed the highest antioxidant capacity. Only Chico and Serr varieties (measured by ABTS+ method) and Franquette variety (measured by ORAC assay) increased their antioxidant capacity when cultured in Torre Blanca plots. The growing in El Chaparral plots increased the antioxidant capacity of every different variety. Minor temperature (especially when it reaches over -0 ºC) and humidity, as well as an increase on the annual rainfall are noteworthy factors that influence on the increase of antioxidant capacity of the wide majority of the analyzed walnuts.